PERILAKU PEMILIH (VOTING BEHAVIOUR) FORUM BETAWI REMPUG (FBR) DALAM PEMILU PRESIDEN INDONESIA 2019 - Daniel Pasaribu; Dina Fadiyah; Nong Ayu Triyanti Utami Hakim; Syarif Fadillah; Alfatri Anom (Universitas Islam Darul Ulum Lamongan, 2022)
This study will discuss the voting behavior of the Betawi Rempug Forum in the 2019 Indonesian Presidential Election. Studies on voter behavior will never stop as long as Indonesia still adheres to a democratic system, as has happened in the Betawi Rempug Forum (FBR) community organization. FBR is a Betawi community organization which in the presidential election changed its political support for Pak Joko Widodo, while during the 2017 DKI Jakarta governor election, they supported the candidate pair for Governor Anies-Sandi. This is what makes a lot of polemics in the community, even every head of the winning team has an argument with each other regarding this. Therefore, it is important to look at the voting behavior of the Betawi Rembug Forum (FBR) in the 2019 Presidential Election. By using the theory of voter behavior and combining it with qualitative research methods with the type of case study research, it is hoped that this study can be a separate contribution. for the study of social science and political science in Indonesia.